Precalculus: Concepts Through Functions, A Unit Circle Approach to Trigonometry (3rd Edition)

Published by Pearson
ISBN 10: 0-32193-104-1
ISBN 13: 978-0-32193-104-7

Appendix A - Review - A.11 Complex Numbers - A.11 Assess Your Understanding - Page A94: 20



Work Step by Step

Multiply each term of the first complex number by each term of the second, then combine like terms and use the fact that $i^2=-1$ to obtain: $$ (5+3i)(2-i)=5(2-i)+3i(2-i) \\=10-5i+6i-3i^2 \\=10+i-3(-1) \\=10+i+3 \\=13+i $$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.